Solubility determination of carbamazepine co-crystals in ethanolic solution at various temperature - Noor Ashila, Ramle (2018)
Co-crystallization is one of the new ways for crystal reformulation highlighted in recent years for weakly ionisable molecules when the traditional approaches, such as salt screening, cannot be achieved. This approach allows binding two or more organic components of an active pharmaceutical ingredient (API) and co-crystal former (CCF) that are, in their pure forms, solids under ambient conditions within one periodic crystalline lattice without breaking or making a new covalent bond. This, in turn, improves the API physicochemical properties and stability while maintaining its structural integrity and therapeutic functions. Carbamazepine (CBZ) is an anticonvulsant and mood-stabilizing drug known for its poor solubility, stability, polymorphism, and bioavailability, which causes problems in dosage consumption in treating patients, was used in this study. This study emphasis on a solubility study of CBZ co-crystals formed with nicotinamide (NIC), saccharin (SAC), succinic acid (SUC), and fumaric acid (FUM) as the CCFs at various temperatures (25-55 °C). Solubility study of the co-crystal system is an important factor in developing and improving the pharmaceutical co-crystallization pathway. High-Performance Liquid Chromatography (HPLC) and gravimetric methods were used to determine the solubility of each component while analytical equipment (X-Ray Powder Diffraction, Diffraction Scanning Calorimetry, Fourier Transform Infrared, and Optical Microscope) were used to characterize the solid crystals and co-crystals formed. The solubility experiment was conducted by the addition of a solid in ethanol solution at different temperatures (25-55 °C) and equilibrates at 72 hours. Based on the data collected, all the crystals formulated are characterized as new crystals believe to be CBZ co-crystals that show different physicochemical properties such as reduction of melting point and distinct morphology. The solubility profiles for all components of CBZ, CCFs and CBZ co-crystals shows the same trend where the solubility values increases as the temperature rises. This finding meets the First Law of Thermodynamics in which heat can facilitate the dissolution process by providing more energy to the system. In addition, the solubility of CBZ-NIC and CBZ-FUM co-crystals were found to be higher than that of pure CBZ crystal, while the solubility of the CBZ-SUC co-crystal was lower than that of pure CBZ crystal for the range of studied temperatures. A different trend was found for the CBZ-SAC co-crystal in which for temperatures lower than 40 °C, the solubility of CBZ crystal is higher, while at temperatures higher than 40 °C, the CBZ-SAC co-crystal has higher solubility than that of the CBZ crystal. The van’t Hoff solubility plot indicates negative deviation behaviour for all crystal components, which shows the existence of an interaction between the solute and the solvent in the system. Findings of this study also show the significant of CCFs screening since different type of API-CCF co-crystals formulated produced different physicochemical properties even same functional group of CCFs is selected.